Vandachostylis ‘Sri-Siam’: an intergeneric hybrid with superior qualities as evidenced by its biochemical fragrance and transcriptome profiles - Mohd Hairul, Ab. Rahim; Ong-Abdullah, Janna; Song, Adelene Ai Lian; Foo, Hooi Ling; Namasivayam, Parameswari; Rahim, Raha Abdul (Springer Science and Business Media LLC, 2022)
Vandachostylis ‘Sri-Siam’ is a fragrant orchid, suitable as a potted plant for the floriculture and perfumery industries due to its sweet citrus-like fragrance. Fragrance from the flowers was captured using SPME and subjected to GC–MS analysis. A transcriptome library was constructed from the tepals for sequencing using the Illumina MiSeq Desktop Sequencer and for de novo assembly using the CLC Genomic Workbench version 6.0. All de novo assembly sequences were subjected to bioinformatics analyses including BLASTx analysis, functional annotations and mapping of the annotated genes/gene products to the KEGG database using the Blast2go Pro software. GC–MS analysis reveals the fragrance are dominated by 68.73% monoterpenes, 11.26% esters, 4.20% sesquiterpenes and traces of alcohols (1.20%), dissimilar to both its parents. Analysis of the de novo assembly sequences generated 45,585 contigs which identified 14 fragrance-related transcripts. Information on the fragrance constituents and fragrance-related transcripts is deemed important as a reference for current and future work of using this hybrid in the breeding process of commercially valuable fragrant orchids.